Power System Analysis of Moving from HVAC to HVDC in the Presence of Renewable Energy Resources - Osama Saadeh; Baher Abu Sba; Zakariya Dalala (Journal of Electrical and Computer Engineering)
As global energy consumption continues to increase, increased utilization and adaptation of renewable energy resources have tremendously increased over the last decades. Unfortunately, despite the many benefits of renewable energy resources, the intermittent nature of generation and the far distance of large installations from demand centers have tremendous effects on the connecting grid’s stability. In this study, high-voltage direct current (HVDC) systems are proposed as a solution for stable and reliable grid operation in the presence of large renewable energy installations. This research investigates the deployment of an HVDC system into an entire network rather than studying it as an isolated radial system. Various power system analysis functions for both static and dynamic conditions are used to study the effect of integrating an HVDC system on the overall network’s stability. To verify the proposed approach, Jordan’s national electric grid was modeled and used as a case study. The results show when deploying HVDC transmission, losses are reduced by 70% from the baseline case, in addition to better handling of contingency events and enhanced grid’s stability when examining the generator’s rotor angle and speed. Rigorous modeling and simulations of the proposed system structure show the feasibility and prove the advantages of modern HVDC systems over HVAC counterparts.